Improving Transparency and Accountability in Public-Private Partnerships Disclosure Diagnostic Report - Kenya (Other Financial Accountability Study, 2018)
Based on research and analysis over the past few years, the World Bank Group Public-Private Partnerships (PPP) Cross-Cutting Solution Area has worked on creating a Framework for Disclosure in Public-Private Partnerships, which suggests a systematic structure for disclosing information proactively at different phases of the PPP process. Two documents, Jurisdictional Studies and Good Practice Cases, have been developed to provide relevant background and resources complementing the goals of the framework. The framework suggests the initiation of work with a PPP Disclosure Diagnostic in countries. The objective of the Diagnostic is to help PPP policy makers and practitioners to assess the status of PPP disclosure in the jurisdiction and identify customized PPP disclosure solutions for all PPP types to enable better disclosure. Under each of the areas identified, the Diagnostic provides the key questions policy makers and practitioners should ask, analysis and techniques for assessing gaps, resources for learning more, and tools for establishing customized PPP disclosure guidelines for the jurisdiction. The relevance of each of the above areas varies based on the unique circumstances within the country. This diagnostic report is structured around the key themes that are relevant to Kenya's disclosure environment